ANALISIS UJI KESELAMATAN LISTRIK DAN KALIBRASI INKUBATOR BAYI DI LABORATORIUM KELISTRIKAN BPFK MEDAN - Gohae, Ramos; Ulina, Sri; Primasyukra, Mhd.Aldi (JURNAL MUTIARA ELEKTROMEDIK, 2024)
Electrical safety test or often referred to as Electrical safety test is a testing process to evaluate whether electrical or electronic devices are safe to use by users. The elements tested include: isolation stage, grounding stage, and leakage current stage. Meanwhile, baby incubator calibration is the process of readjusting the device to provide accurate results in measuring temperature, humidity and air pressure in a certain environment. The importance of electrical safety tests and calibration of baby incubators is to minimize the risk of accidents and errors in their use, especially in babies who are susceptible to changes in environmental conditions. Therefore, the electrical safety test process and calibration of the baby incubator must be carried out regularly and periodically.